Bacterial communities associated with Brassica napus L. grown on trace element‐contaminated and non‐contaminated fields: a genotypic and phenotypic comparison. Issue 4 (18th April 2013) - Croes, S.; Weyens, N.; Janssen, J.; Vercampt, H.; Colpaert, J.V.; Carleer, R.; Vangronsveld, J.
Summary Cultivable bacterial strains associated with field‐grown Brassica napus L. (soil, rhizosphere and roots) from a trace elements (Cd, Zn and Pb) contaminated field and a non‐contaminated control field were characterized genotypically and phenotypically. Correspondence analysis of the genotypic data revealed a correlation between soil and rhizosphere communities isolated from the same field, indicating that local conditions play a more important role in influencing the composition of (rhizosphere) soil bacterial communities than root exudates. In contrast, endophytic communities of roots showed a correlation between fields, suggesting that plants on the two fields contain similar obligate endophytes derived from a common seed endophytic community and/or can select bacteria from the rhizosphere. The latter seemed not very likely since, despite the presence of several potential endophytic taxa in the rhizosphere, no significant correlation was found between root and rhizosphere communities. The majority of Cd/Zn tolerant strains capable of phosphorus solubilization, nitrogen fixation, indole‐3‐acetic acid production and showing 1‐aminocyclopropane‐1‐carboxylate deaminase capacity were found in the rhizosphere and roots of plants growing on the contaminated field.